(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The essay deals with the death of DJ Fabiano Antoniani (DJ-Fabo), who travelled to Switzerland to commit assisted suicide and with the subsequent criminal proceedings initiated by the Italian public prosecution (Procura della Republica) of Milan against Marco Cappato for allegedly helping him in committing suicide (crime severely punished by Article 580 of the Italian Criminal Code). After analyzing the measures of the public prosecutors and the GIP of Milan, based on a careful study of the Italian and supranational jurisprudence, the article tries to answer the question on the compatibility of the right to die with dignity with Italian law, and on the consequences it could produce in the process concerning Cappato’s case and, in general, in terms of active euthanasia.